Outcomes of induction chemotherapy followed by chemoradiation using intensity-modulated radiation therapy for esophageal adenocarcinoma. Issue 3 (1st April 2014) - Gerber, N.; Ilson, D. H.; Wu, A. J.; Janjigian, Y. Y.; Kelsen, D. P.; Zheng, J.; Zhang, Z.; Bains, M. S.; Rizk, N.; Rusch, V. W.; Goodman, K. A.
Summary: This study looks at toxicity and survival data when chemoradiation (CRT ) is delivered using intensity-modulated radiation therapy (IMRT ) after induction chemotherapy. Forty-one patients with esophageal adenocarcinoma treated with IMRT from March 2007 to May 2009 at M emorial S loan-K ettering C ancer C enter were analyzed. All patients received induction chemotherapy prior to CRT . Thirty-nine percent ( n = 16) of patients underwent surgical resection less than 4 months after completing CRT . Patients were predominantly male (78%), with a median age of 68 years (range 32–85 years). The majority of acute treatment-related toxicity was hematologic or gastrointestinal, with 17% of patients having grade 3+ hematologic toxicity and 12% of patients having grade 3+ gastrointestinal toxicity. Only two patients developed grade 2–3 pneumonitis (5%) and 5 patients experienced post-operative pulmonary complications (29%). Eight patients (20%) required a treatment break. With a median follow up of 41 months for surviving patients, 2-year overall survival was 61%, and the cumulative incidences of local failure (LF ) and distant metastases were 40% and 51%, respectively. This rate of LF was reduced to 13% in patients who underwent surgical resection. Surgery and younger age were significant predictors of decreased time to LF on univariate analysis. Induction chemotherapy followed by CRT using IMRT in the treatment of esophageal cancer is well tolerated and is not associated with an elevated risk of postoperative pulmonary complications. The use of IMRT may allow for integration of more intensified systemic therapy or radiation dose escalation for esophageal adenocarcinoma, ultimately improving outcomes for patients with this aggressive disease.